An Authentic Learning Approach to Assist the Computational Thinking in Mathematics Learning for Elementary School - Ratna Wardani; Masduki Zakaria; Priyanto Priyanto; Muhammad Irfan Luthfi; Irma Nuur Rochmah; Andy Ferry Rahman; Muhammad Trio Maulana Putra (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
Programme for International Student Assessment (PISA) 2018 report revealed that in mathematics the ability of Indonesian students to solve mathematical problems is still very low. The Trends in International Mathematics and Science Study (TIMSS) strengthened the PISA report by mentioning that in general, Indonesian students' ability in solving fraction problems is low. In this study, We tried to improve students' ability in solving fractions by using computational thinking assisted by an authentic learning approach. A system was utilized to help the students in learning fractions. Totally twenty-two fifth-grade students were assigned in this study. While they learned fractions using the system, they needed to capture an object around them to make a representation of the fraction problem. Moreover, by using the system, they also need to find the best and fastest way to solve a fraction problem. The result showed that their learning achievements improved especially in fraction representation, fraction operation, linguistics, and creativity. And multiple regression results showed that students’ activity can predict the students’ learning achievement. The more active the learn fraction using the system, the higher score they get. In the final, the result of this study contributes essential implications along with a conclusion and suggestion for future research.